Inventarisasi Tanaman Obat dalam Pengobatan Tradisional di Kecamatan Duhiadaa, Kabupaten Pohuwato - Irwan Nooyo; Yulan Ismail; Umar, Opriyanto (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
The use of medicinal plants has been an important part of people's lives since the time of our ancestors. Before the advent of modern medicine, people used various types of plants to treat mild to severe illnesses, such as fever, cough, wounds, digestive disorders, and skin diseases. Inventory of medicinal plants plays a very important role in exploring the potential of existing natural resources, especially as an effort to support the development of traditional medicine. The purpose of this study is to identify the types of medicinal plants used by local communities in traditional medicine. The method used in this study is a descriptive method through direct surveys at the research location. The findings obtained in the field concluded that all types of plants mentioned in this study are very beneficial for the people of Duhiadaa District, because they can help in treating various types of diseases experienced by the community. The types of diseases that can be treated include hypertension, gout, stomach acid, cholesterol, kidney disease, diabetes, inflammation, cancer, wounds, diarrhea and digestive disorders.